Designing a Business Strategy Using the Business Model Canvas (BMC) Study on The Jangji Application - Rahmah, Rosyidah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
The business model is a crucial aspect of building a business. The Wedding Organizer (WO) business is getting back on its feet as social restrictions are lifted during the Covid 19 pandemic. Jangji is a one-stop application built to select and use WO and Wedding Planner services. The purpose of this research is to project the Jangji business model and design a business model using the Business Model Canvas approach. The method used in this research is descriptive method with a case study approach. The steps taken are: (1) SWOT Analysis, (2) Grand Strategy Analysis, (3) Business Model Canvas. This research found that the right strategy to apply to this business is the Growth and Stability Strategy, where Jangji can add more application features, take advantage of the momentum as a pioneer and publish tools in applications through digital marketing. It is hoped that the BMC mapping in this research can help the development of Jangji's business model.